Using of Hierarchical Loglinear Model in Multiway Frequency Tables and an Application on Suicide Cases - Fatih Üçkardeş (Sakarya University Journal of Computer and Information Sciences, 2022)
The aim of this study was to use Hierarchical Loglinear Model (HLLM) in the analysis of multiway frequency tables and to interpret the main and interaction effects of this model on suicide cases. The data set used in this study was taken from the Turkish Republic State Statistical Institute (TUIK). A total of 6479 cases in 2016 and 2018 years were used in this analysis and the analyzes were made by considering gender, year and age variables. As a result of HDLM analysis, Year, Gender and Age, which are the main effects in suicide cases, and the interactions of Year × Gender and Gender × Age were found significantly (P